2018
DOI: 10.1021/acs.biochem.8b00644
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Spectroscopic Characterizations of a Hybrid Light-Harvesting Reaction Center Core Complex

Abstract: The light-harvesting 1 reaction center (LH1-RC) complex from Thermochromatium tepidum exhibits a largely red-shifted LH1 Q absorption at 915 nm due to binding of Ca, resulting in an "uphill" energy transfer from LH1 to the reaction center (RC). In a recent study, we developed a heterologous expression system (strain TS2) to construct a functional hybrid LH1-RC with LH1 from Tch. tepidum and the RC from Rhodobacter sphaeroides [Nagashima, K. V. P., et al. (2017) Proc. Natl. Acad. Sci. U. S. A. 114, 10906]. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…2−4 Interestingly, however, recent studies using a heterologously expressed hybrid LH1-RC complex reported that the uphill energy transfer rate indeed depends on the extent of the energy gap. 6,7 In some purple bacteria, decreasing the LH1 Q y transition energy is largely involved in the uphill energy gap. For example, the purple bacteria Roseospirillum (Rss.)…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…2−4 Interestingly, however, recent studies using a heterologously expressed hybrid LH1-RC complex reported that the uphill energy transfer rate indeed depends on the extent of the energy gap. 6,7 In some purple bacteria, decreasing the LH1 Q y transition energy is largely involved in the uphill energy gap. For example, the purple bacteria Roseospirillum (Rss.)…”
mentioning
confidence: 94%
“…The ringlike LH1 encircles the RC to form an LH1-RC complex, in which uphill energy transfer from LH1 to the RC occurs against the energy barrier . The reaction mechanisms of the uphill energy transfer have been investigated by time-resolved spectroscopic measurements. Previous studies demonstrated that the rate of uphill energy transfer in purple bacteria is essentially independent of the energy gap between the LH1 and RC complexes. Interestingly, however, recent studies using a heterologously expressed hybrid LH1-RC complex reported that the uphill energy transfer rate indeed depends on the extent of the energy gap. , …”
mentioning
confidence: 99%
“…This red shift correlates with the presence of tightly bound Ca 2+ ion, one co-ordinated in the space between each αβ-dimer in the C-terminal loop region, Figs. 1 c and 4 b top (Kimura et al 2008 , 2009 ). The ends of the αβ-polypeptides in RC–LH1 (and LH2) complexes are, generally, quite flexible and may not be visible in the electron density maps.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other divalent cations can substitute for Ca 2+ in the Tch. tepidum RC–LH1 ‘Core’ complex (Kimura et al 2018 ). The structure of this complex has also been solved with either Sr 2+ or Ba 2+ substituting for Ca 2 + (Yu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that this “uphill” energy transfer in the hybrid strain occurs with an efficiency of 48%, which, surprisingly, is even greater than that observed in Rba. sphaeroides wild type (40%) . However, an unanswered question is whether this high efficiency shown in vitro is also reflected in vivo as measured by phototrophic growth.…”
mentioning
confidence: 99%